Effects of Peer Education, Education by Physician and Giving Pamphlets on HIV Knowledge in High School Students: A Comparative Study - A Azizi; F Amirian; M Amirian (Tehran University of Medical Sciences, 2008)
Background & Aim: Youths are the most at risk group for HIV/AIDS in the world and education of the preventive measurements is the most effective way for decreasing the incidence of HIV/AIDS among them. Due to ever-increasing cases of HIV and the importance of education, we compared the effects of three educational methods (peer education, education by physician and giving pamphlets) on knowledge of female high school students;apos of Kerman shah on HIV/AIDS. Methods & Materials: One thousand and five hundred female third grade students were recruited from 21 high schools using stratified random sampling method. An average of 73 students were selected from each school and participated in a pre-test exam using a questionnaire. Of 1500 students, 498 and 502 students were taught by general practitioners and peers, respectively. Pamphlets were presented to 500 other students. Twenty days after the educational intervention, the participants were contributed in a post-test exam using the very questionnaire. Data were analyzed using descriptive and inferential statistics via SPSS version 11.5. Results: The students;apos mean age was 16.78 (SD=0.7). The mean scores of pretests and post-tests in all 3 groups were significantly different (P<0.001). The mean score for the group taught by general practitioners (10.7±3.6) was higher than the scores of other two group scores (8.8±3.4 and 7.3±3.9, respectively for peer education and pamphlet groups) after the interventions. Bonferroni statistical test showed the significant difference (P<0.001). Conclusion: Education presented by general practitioners seems to be more effective than the other two ways in increasing students;apos knowledge about HIV/AIDS.